2004
DOI: 10.4088/jcp.v65n0918a
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-Up of a Patient With Successful Continuation of Clozapine Treatment Despite Morning Pseudoneutropenia

Abstract: Sir: Agranulocytosis occurs in 1% to 2% of patients treated with clozapine. Thus, if neutropenia (absolute neutrophil count [ANC] of < 1500/µL) occurs during clozapine treatment, physicians generally interrupt the drug treatment and do not reintroduce it. Lithium and granulocyte colony-stimulating factor may be used to reverse clozapine-induced granulocytopenia. 1 We have previously reported the case of a patient who was able to continue clozapine treatment despite developing "morning pseudoneutropenia" (MPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In one such patient the leucocyte results were 2.9-4.2 L À9 in the morning and 3.6-7.1 L À9 in the afternoon, with granulocytes 0.8-1.4 L À9 and 2.9-5.5 L À9 , respectively (Ahokas and Elonen, 1999). Circadian variations in the number of circulating neutrophils have also been described in several non-Jewish Caucasians (Esposito et al, 2004(Esposito et al, , 2005a. Clozapine may thus be withdrawn unnecessarily unless account is taken of this phenomenon.…”
Section: Clozapine and Neutropeniamentioning
confidence: 85%
“…In one such patient the leucocyte results were 2.9-4.2 L À9 in the morning and 3.6-7.1 L À9 in the afternoon, with granulocytes 0.8-1.4 L À9 and 2.9-5.5 L À9 , respectively (Ahokas and Elonen, 1999). Circadian variations in the number of circulating neutrophils have also been described in several non-Jewish Caucasians (Esposito et al, 2004(Esposito et al, , 2005a. Clozapine may thus be withdrawn unnecessarily unless account is taken of this phenomenon.…”
Section: Clozapine and Neutropeniamentioning
confidence: 85%
“…20 It is unclear why MPN occurs with clozapine treatment, but one thought is that clozapine may make the circadian differences in circulating neutrophils more pronounced. 24 Providers may want to have the blood drawn in midmorning or afternoon to avoid discontinuing clozapine because of this effect. The addition of lithium has been used in both pediatric and adult patients with schizophrenia having clozapine-induced neutropenia.…”
Section: Anti-infectivesmentioning
confidence: 99%
“…Environmental factors also must be considered but as yet have not been systematically evaluated. For example, there is evidence that fluctuations in circadian rhythm impact the number of circulating neutrophils in patients [37,81]. Along similar lines, it has been demonstrated that moderate exercise increases white blood cell count [37], and typical schizophrenia patients usually have lower interest in exercise.…”
Section: Discussionmentioning
confidence: 91%